The Unusual Ultrasound Features of a Breast Cholesterol Granuloma Manifesting as an Intracystic Mass: Case Report and Literature Review - Ahn, Hye Shin (The Korean Society of Radiology, 2013)
Cholesterol granuloma of the breast is a rare, benign disease. Here, we present the unique ultrasonographic findings of breast cholesterol granuloma manifesting as an intracystic mass. The findings of this case report may help expand existing knowledge regarding differential diagnosis of intracystic breast masses, which are found on ultrasonographic examination.